Biomimetic S‐Adenosylmethionine Regeneration Starting from Multiple Byproducts Enables Biocatalytic Alkylation with Radical SAM Enzymes. (4th April 2023) - Gericke, Lukas; Mhaindarkar, Dipali; Karst, Lukas C.; Jahn, Sören; Kuge, Marco; Mohr, Michael K. F.; Gagsteiger, Jana; Cornelissen, Nicolas V.; Wen, Xiaojin; Mordhorst, Silja; Jessen, Henning J.; Rentmeister, Andrea; et al.
Abstract: S ‐Adenosylmethionine (SAM) is an enzyme cofactor involved in methylation, aminopropyl transfer, and radical reactions. This versatility renders SAM‐dependent enzymes of great interest in biocatalysis. The usage of SAM analogues adds to this diversity. However, high cost and instability of the cofactor impedes the investigation and usage of these enzymes. While SAM regeneration protocols from the methyltransferase (MT) byproduct S ‐adenosylhomocysteine are available, aminopropyl transferases and radical SAM enzymes are not covered. Here, we report a set of efficient one‐pot systems to supply or regenerate SAM and SAM analogues for all three enzyme classes. The systems' flexibility is showcased by the transfer of an ethyl group with a cobalamin‐dependent radical SAM MT using S ‐adenosylethionine as a cofactor. This shows the potential of SAM (analogue) supply and regeneration for the application of diverse chemistry, as well as for mechanistic studies using cofactor analogues. Abstract : The biomimetic regeneration system for S ‐adenosylmethionine (SAM) and SAM analogues presented is based on the salvage of the adenine moiety and in situ supply of d ‐ribose and polyphosphate. It is compatible with a broad range of SAM‐dependent enzymes including aminopropyl transferases, and is shown to support ethylation reactions with both conventional and radical SAM methyltransferases.